KEPENTINGAN EKONOMI POLITIK NIGERIA MENJALIN KERJASAMA BIDANG PERKEBUNAN KELAPA SAWIT DENGAN INDONESIA TAHUN 2011 - Rahmi, Maulida; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The purpose of this research is to understand how Nigeria political-economy interest. Nigeria is known as the largest oil exporter country and the largest non-oil imports. Non oil-sector, Nigeria imports much consumer good. Consumer good are made from palm oil agriculture sector or non-oil. This phenomenon makes Nieria wants to establish cooperation with Indonesia in the palm plantation in 2011. Thus researcher question is how the politic-economy interest of Nigeria in this corporation with Indonesia.This research theoretically has built with liberalism perspectives on International Relations and supported by international coorporation theory and International trade theory. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Technique in this research is through by the study of library.Data which is gotten and collected through the journal books, the last thesis and then from internet has related to the problems.Researcher has formulated answered-hypothesis whic reveals the fact that the politic-economy interest of Nigeria in the Palm Plantation coorporation with Indonesia have 4 interests. The First, Nigeria wants to increase non-oil sector. Second, Nigeria wants to tight their bilateral relation with Indonesia. Third, Nigeria wants to increase their value of trade based on export and import. Forth, Nigeria wants to increase value of investment Indonesia to Nigeria.Keywords : Interest, economic-politic, Nigeria, Coorperation, Indonesia, Palm